Judicial Rescission of a Preliminary Sales Agreement Due to Abuse of Circumstances: Pembatalan Secara Yudisial terhadap Perjanjian Pendahuluan Jual Beli karena Penyalahgunaan Keadaan - Aripin, Clarissa; Tjempaka, Tjempaka (Academia Open, 2026)
General Background: The Sale and Purchase Binding Agreement (PPJB) as a notarial authentic deed serves as a legal instrument to facilitate land transactions and ensure legal certainty in civil law practice. Specific Background: In practice, PPJB may not always reflect a balanced agreement, particularly when one party experiences inequality of position, leading to misbruik van omstandigheden or abuse of circumstances. Knowledge Gap: Despite formal validity, there remains limited analysis of judicial reasoning in assessing defects of consent within PPJB and the resulting legal consequences in Indonesian court decisions. Aims: This study analyzes the judge’s legal considerations in annulling a notarial PPJB due to abuse of circumstances and examines the legal consequences of such annulment in Decision Number 234/Pdt.G/2020/PN Mtr. Results: The findings indicate that the annulment is based on a defect of consent arising from unequal bargaining positions, where the agreement did not reflect a freely formed will as required under Article 1320 of the Indonesian Civil Code. Consequently, the PPJB is categorized as a voidable agreement (vernietigbaar), resulting in the loss of binding legal force after the court decision and restoring the parties to their original position. Novelty: This study highlights the judicial application of misbruik van omstandigheden as a doctrinal basis for evaluating substantive justice beyond formal legality in notarial deeds. Implications: The findings emphasize the need for notarial prudence and consistent judicial application of abuse of circumstances doctrine to ensure legal protection for weaker parties in contractual relations. Highlights: Court reasoning confirms imbalance of bargaining positions as basis for contract invalidation. Agreement classification as vernietigbaar leads to loss of legal enforceability after judgment. Legal status of parties is restored to pre-contractual condition following annulment. Keywords: PPJB Annulment, Misbruik Van Omstandigheden, Notarial Deed, Defect of Consent, Indonesian Civil Law